RISK MANAGEMENT IMPLEMENTATION PRACTICES IN RUSSIAN INDUSTRIAL COMPANIES: RESULTS OF AN EMPIRICAL STUDY - M. O. Kuznetsova (Стратегические решения и риск-менеджмент)
The article analyzes the practice of implementing risk management in Russian industrial companies. The study conducted a survey of 96 industrial companies in various industries in order to identify the features of implementing a risk management system in Russian industrial organizations. The main goals of implementing risk management systems in industrial companies, the features of organizational risk management structures, the amount of costs for maintaining risk management systems, risk assessment methods, the activities of industrial organizations that integrate risk management processes, and the level of automation of risk management systems were identified.The method of assessing the level of maturity of risk management is proposed: absent, managed, quantitatively managed, optimized and advanced levels.Using cluster analysis, groups of Russian industrial companies in various industries were identified by the level of process maturity of the risk management system. The most developed in the field of risk management systems are companies in the mining industry, mechanical engineering, as well as those engaged in the production of consumer goods. Companies with the least developed level of risk management include companies in the furniture, pulp and paper, cosmetics, and pharmaceutical industries, as well as those that produce building materials.On the basis of the survey identified the main barriers introducing a comprehensive system of risk management of industrial companies.The described research areas will help to increase the effectiveness of the risk management system, which will help to increase the strategic stability of the company.